(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
Hygromycin B was extracted with ethyl acetate, which separates organic phase from aqueous phase in the broth culture filtrate, only the aqueous phase showed significant antimicrobial activity by using agar well diffusion technique. At a concentration of 25mg/ml (as crude extract), this phase excreted its activity against the test microorganisms which include; one G(+) bacteria (Staphylococcus aureus), five G(–) bacteria (Pseudomonas aeruginosa , Proteus mirabilis, Escherichia coli , Klebsiella pneumoniae, Salmonella typhi) and one yeast (Saccharomyces cerevisiae). After detecting the aminoglycoside hygromycin B by the Thin Layer Chromatography (TLC) method to ensure presence of the antibiotic, same flow rate (Rf) value (0.357) as that of the standard hygromycin B was obtained. Results of the optimization conditions showed that the highest antimicrobial activity of hygromycin B was obtained at a medium pH of 8 and incubation temperature of 35°C for 10 days. When the toxicity of hygromycin B crude extract under such conditions was examined on mice liver, a mild effects were appeared